Semisynthesis: Bridging natural products and novel anticancer therapies - Goel B.; Jain S.K. (My University, 2025)
Natural products (NPs) have played a central role in drug discovery particularly in therapeutic areas like oncology, and infectious diseases. Despite their pharmacological potential, natural products present some significant challenges for therapeutic applications, such as toxicity, pharmacokinetic characteristics, supply problems, and drug resistance. Some of these issues have been solved by semisynthetic derivatives of natural products, and many semisynthetic drugs have been developed and approved for clinical use. Repeatedly, it has been observed that outcomes of semisynthetic modifications of natural products retain the medicinal activity of the parent compound while altering other characteristics such as toxicity and oral bioavailability, escalating their momentum of reaching the market. This review describes NP-derived semisynthetic anticancer drugs approved from 1981 to 2023. The review also confers the advantages of semisynthetic modifications of natural products, including supply fulfillment, improved pharmacokinetics (increased bioavailability, plasma half-life, etc.), improved solubility and lipophilicity, reduced toxicity, enhanced selectivity, and reduced resistance. © 2024 The Authors